2020
DOI: 10.1177/0008417420922635
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Older Adults’ Experiences and Perceptions with a Peer-Led Wheelchair Training Program

Abstract: Background. Manual wheelchair (MWC) training is important, but less than 50% of new wheelchair users receive any training. The Wheelchair training Self-efficacy Enhanced for Use (WheelSeeU), a community-based peer-led MWC training program, is feasible and effective for improving wheelchair skills. However, implementing effective programs requires an understanding of stakeholders’ experiences. Purpose. Explore older adults’ perceptions about their participation in the WheelSeeU program. Method. Qualitative inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Studies have suggested the potential power of peer and group approaches, respectively for providing mentorship and support for people with disability, including wheelchair users [35,[58][59][60]. The power of these approaches may extend to children and adolescents as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have suggested the potential power of peer and group approaches, respectively for providing mentorship and support for people with disability, including wheelchair users [35,[58][59][60]. The power of these approaches may extend to children and adolescents as well.…”
Section: Discussionmentioning
confidence: 99%
“…Peers share life experiences and are perceived as a credible source of information [59]. Moreover, the vicarious experience that is provided by watching the peer-trainers and the other participants of the group can strengthen self-efficacy in one's ability to learn new skills and can influence behaviour changes (e.g., wheelchair use) [35,60]. Gowran et al, reported parent perceived benefits of their child interacting with an adult wheelchair user, such that watching another person successfully perform skills fostered their children's belief in their own potential and revealed skills that were unimaginable before [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings indicated that "resistance training improved functional independence while both types of exercise (aerobic arm-ergometer and resistance training) included positive effects on quality of life" (Willig et al, 2020). One more example of the success of training programs can be found in a 2020 article by Pellichero et al (2020) which studied 11 individuals and conducted rehabilitation training programs to improve satisfaction and self-sufficiency. Their study found that all the participants "expressed satisfaction and quality of participation with the WheelSeeU program that increased autonomy, improved (Manual Wheelchair) MWC mobility and self-efficacy, and enhanced social connectedness" (Pellichero et al, 2020).…”
Section: Training Programsmentioning
confidence: 99%
“…One more example of the success of training programs can be found in a 2020 article by Pellichero et al (2020) which studied 11 individuals and conducted rehabilitation training programs to improve satisfaction and self-sufficiency. Their study found that all the participants "expressed satisfaction and quality of participation with the WheelSeeU program that increased autonomy, improved (Manual Wheelchair) MWC mobility and self-efficacy, and enhanced social connectedness" (Pellichero et al, 2020). Charlton et al published a pilot study in 2021 which sought to explore how a wheelchair skills training program could affect performance, confidence and CP for MWU.…”
Section: Training Programsmentioning
confidence: 99%